Application of fuzzy RES and fuzzy DEMATEL in the rock behavioral systems under uncertainty. Issue 1 (2nd January 2019) - Rafiee, Ramin; Mohammadi, Sadjad; Ataei, Mohammad; Khalookakaie, Reza
Abstract: Most of the mine design methods, especially in underground mining depend on the rock mechanics and thus, they are based on rock behavioral systems. Existence of uncertainty in the rock physical and mechanical parameters leads this assessment to be impossible. In such situation, the system thinking methods can be useful. The aim of this paper is to apply system thinking-based techniques for assessment of the rock mass cavability in block caving mines. For this purpose, fuzzy rock engineering system (FRES) and the decision-making trial and evaluation laboratory (FDEMATEL) methods are used to investigate caving behavioral system. The interrelationships and structure of the parameters involved in the rock mass cavability were determined by these methods. In addition, the parameters were categorized from causality point of view and ranked due to their importance. Finally, two methods were compared in the studying a complex system like the cavability of rock masses from their advantages and disadvantages point of view. This study shows that such analysis is useful in practice to better understanding rock behavior and its impact on the working space regard to the safety and the productivity.